Various Dosage Forms of Tridax Procumbens and their Antimicrobial Activity Against Specific Pathogens - Swati Ambulkar1 , Pranit Ambulkar2 , Manish P. Deshmukh3 , Ashish B. Budhrani4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: TridaxProcumbens Linn, (Tridax) is a herb traditionally used in Indian traditional medicinefor different ailments like cough, cold, amoebiasis and most importantly for seizing the bleeding and woundmanagement. Practically it is observed that the wound treated with Tridax was found to be very rarelyinfected and healed properly. Researched suggests that the different dosage form of the Tridax have differentpotential in wound healing. On these two backgrounds, the hypothesis was made that the Tridax has gotantimicrobial property and the antimicrobial potential varies as per the dosage form.Method: To examine the hypothesis, in the present experiment, seven Ayurvedic dosage forms of Tridaxviz. fresh leaves juice, fresh flower juice, fresh root juice, aqueous decoction, medicated oil, medicatedGhee, ash, alkaline aqueous water-soluble fraction of the Ash and six organic solvent extracts of Tridaxviz. ethanol, methanol, chloroform, ethyl acetate, benzene and petroleum ether were tested for theirantimicrobial activity against eleven different disease-causing microbes viz. Bacillus subtilis, Proteusvulgaris, Shigellaflexneri Staphylococcus aureus, Enterobacter aerogenes, Chryseobacteriumgleum,Klebsiella pneumoniae, Aspergillus fumigatus, Candida albicans, Aspergillus niger and Aspergillus flavus.Antimicrobial experiment was carried out with appropriate nutrient media and disc diffusion method.Results: Leaf juice showed microbial inhibition zone of 28mm against B. subtilis. Flower juice showed17mm against C. albicans, aqueous decoction showed 14mm against C. gleum, Ethanol extract, Methanolextract, Chloroform ext. and Ethyl act. Extract showed microbial inhibition zone of 17mm, 14mm and14mm against respectively.Conclusion: The different dosage form of Tridax have a different and significant antimicrobial potentialagainst different microbes. It supports the importance of different processing suggested in classical Ayurvedictext for obtaining different results from aparticular herb.